Advances in Mechanical and Power Engineering II Selected Papers from The International Conference on Advanced Mechanical and Power Engineering (CAMPE 2023), October 16-19, 2023 - Altenbach, Holm; Gao, Xiao-Wei; Syngellakis, Stavros; Cheng, Alexander H.-D; Lampart, Piotr; Tkachuk, Anton (Lecture Notes in Mechanical Engineering, 2025)
XX, 326 p. 136 illus., 91 illus. in color.